Effect of N-Acetyl Cysteine, Selenium and Zinc as Oral Nutritional Supplement on Reproductive Performance in Local Iraqi Ewes. - M. H. Huwaish; T. R. Mohammed (مجلة الانبار للعلوم البيطرية)
The study aimed to investigate the effect of the administration N-acytl cysteine to ewes with or without selenium and zinc on reproductive performance and the level of estrogen and progesterone hormones for local ewes. 24 local ewes were used, 3-5 of age and weighing 45-55 kg. They were randomly distributed to 4 groups, 6 ewes for each one. All ewes were treated six days before pushing the vaginal sponges and continued for 45 days. The Group 1 (T1) was treated with (10 mg N-acytl cysteine/kg body weight), Group 2 (T2) was treated with (10 mg N-acytl cysteine/kg body weight + 0.03 mg selenium/kg body weight), Group 3 (T3) was treated with (10 mg N-acytl cysteine/ kg of body weight + 0.03 mg zinc/kg of body weight) while the Group 4 (T4) was left without treatment (control group). The results showed a significant increased (p≤0.05) of treatment (T1) at the time of first estrus, followed by the control treatment, then treatment (T2, T3). Results recorded a significant increased (p≤0.05) of T1, T3 and T2 respectively in estrus rate. Furthermore, the treated group showed a significant increased (p≤0.05) compared with the control group in the fertilization %pregnancy, the percentage of twins, births and the number of births. The supplement N-acetyl cysteine with selenium or zinc led to an improvement in reproductive performance